Socio Psychological Factors As A Panacea To Adolescent’ Social And Health-Related Preventive Practices Of Corona Virus In Ibadan South West, Oyo State Nigeria. - Tokede, Abiodun Morenike; Rose, Appah Ogechukwu (Advances in Social Sciences Research Journal, 2020)
The Corona Virus pandemic has evolved and continues to be a very serious emergency across the globe. It is observed that many people do not take the prevention of this disease seriously, thus this study focused on the influence of demographic factors, corona virus awareness, and perception on social and health-related preventive practices of secondary school adolescents in Ibadan south west Local Government Area in Oyo state, Nigeria. The survey was conducted on one hundred and sixty (160) adolescents selected from four (4) private and four (public) secondary schools in Ibadan southwest LGA using a two-stage random sampling procedure. The instrument for data collection is a questionnaire titled Awareness, Perception and Adolescents’ Social and Health- Related Preventive Practices of Corona virus (APSHRPCV). It was used to obtain information on demographic factors, awareness (R=0.86), perception (R=0.84) and social and health-related preventive practices (R=0.83). Data was analysed using descriptive (frequency, mean and standard deviation) and inferential statistics (Pearson moment correlation and regression analysis). The result revealed low level of adolescents’ Covid-19 social and health-related preventive practices. It was observed that relationship between their awareness and perception of COVID-19 is a positive low relationship. Also it was revealed that awareness and perception can predict adolescents’ social and health-related preventive practices. It is, therefore, recommended that the Nigeria Centre for Disease Control (NCDC) put in place more campaigns through adolescents’ friendly social media to increase their awareness and perception, since positive awareness and perception is found to enhance adolescents’ Covid-19 social and health-related preventive practices.